Why cachexia kills: examining the causality of poor outcomes in wasting conditions. Issue 2 (8th June 2013) - Kalantar-Zadeh, Kamyar; Rhee, Connie; Sim, John J.; Stenvinkel, Peter; Anker, Stefan D.; Kovesdy, Csaba P.
Abstract : Weight loss is the hallmark of any progressive acute or chronic disease state. In its extreme form of significant lean body mass (including skeletal muscle) and fat loss, it is referred to as cachexia. It has been known for millennia that muscle and fat wasting leads to poor outcomes including death. On one hand, conditions and risk factors that lead to cachexia and inadequate nutrition may independently lead to increased mortality. Additionaly, cachexia per se, withdrawal of nutritional support in progressive cachexia, and advanced age may lead to death via cachexia‐specific pathways. Despite the strong and consistent association of cachexia with mortality, no unifying mechanism has yet been suggested as to why wasting conditions are associated with an exceptionally high mortality risk. Hence, the causality of the cachexia–death association, even though it is biologically plausible, is widely unknown. This century‐long uncertainty may have played a role as to why the field of cachexia treatment development has not shown major advances over the past decades. We suggest that cachexia‐associated relative thrombocytosis and platelet activation may play a causal role in cachexia‐related death, while other mechanisms may also contribute including arrhythmia‐associated sudden deaths, endocrine disorders such as hypothyroidism, and immune system compromise leading to infectious events and deaths. Multidimensional research including examining biologically plausible models is urgently needed to investigate the causality of the cachexia–death association.